A survey of user experience practice: A point of meet between academic and industry - Hussein, Idyawati; Mahmud, Murni; Md Tap, Abu Osman (IEEE, 2014)
This paper reports a questionnaire survey which is conducted at the iUser Conference in 2011. The iUser 2011 conference is expected to be the platform to discover the usability and user experience design practitioners from both academic and industry settings in Malaysia. A survey is adopted from the literature that attempted to assess the practice of user-centered design among Human-Computer Interaction (HCI) practitioners. The results reveal a contrary findings to the characteristics of attendees of HCI-focused conference in other countries. While the practice of user experience has gained more attention, usability issues is still at its infancy. The attendees were new to the terminologies and still learning on the fundamental of usability and user experience. The results show that the conference participants were unable to represent the HCI practitioners in the local settings. Consequently, in order to study the practice of user experience, researchers need to locate the right HCI practitioners who qualified to be classified as the community of practice who shared the same values towards embedding the user experience techniques in the existing technology development process.